Human trophoblast invasion: new and unexpected routes and functions - Moser, Gerit (Histochem Cell Biol, 2018)
Until recently, trophoblast invasion during human placentation was characterized by and restricted to invasion into uterine connective tissues and the uterine spiral arteries. The latter was explained to connect the arteries to the intervillous space of the placenta and to guarantee the blood supply of the mother to the placenta. Today, this picture has dramatically changed. Invasion of endoglandular trophoblast into uterine glands, already starting at the time of implantation, enables histiotrophic nutrition of the embryo prior to perfusion of the placenta with maternal blood. This is followed by invasion of endovenous trophoblasts into uterine veins to guarantee the drainage of fluids from the placenta back into the maternal circulation throughout pregnancy. In addition, invasion of endolymphatic trophoblasts into the lymph vessels of the uterus has been described. Only then, invasion of endoarterial trophoblasts into spiral arteries takes place, enabling hemotrophic nutrition of the fetus starting with the second trimester of pregnancy. This new knowledge paves the way to identify changes that may occur in pathological pregnancies, from tubal pregnancies to recurrent spontaneous abortions.